KONSTRUKSI HUKUM YANG BERSUMBER DARI REALITAS SOSIAL (Suatu Implikasi Terhadap Sosiologikal Jurisprudensi) - Andi Kasmawati (Faculty of Law, Universitas Diponegoro, 2011)
Responsiveness Law which has been developed by Nonet and Selznick is the main idea of Law of Realism which developed by Holmes and friends in Realism of American and Realism of Skandinavian, which has been developed by Ross and friends. Their opinion about law of realism is a law which start from the empirical reality, re/ism is shown as the fight against logical theory, who seen the law as what's on the ammandement. In this theory, the judge isnY free to form the law but just finding the law. This opinion been the focus of Teubner as the basic to construct the law as the implication of